MODELING OF VOLCANO ERUPTION RISK TOWARD BUILDING DAMAGE PROBABILITY AND AFFECTED POPULATION - AYU RETNOWATI (NIM: 25116004), DYAH
Indonesia has 127 active volcanoes, around 60% of these active volcanoes are potentially hazardous for surrounding. Risk assessment of volcanic eruption should be applied to reduce the impact of the eruption in the future, including damage loss and affected population. Risk assessment for future need to involve land cover change. This component will affect the condition of exposure toward hazard. This research use three area studies based on characteristic of land cover around the volcanoes; Guntur, Marapi, and Rinjani, which is close to urban area, around rural area, and far from settlement area, consecutively. There are three main data that should be known to asses risk, hazard data, vulnerability data, and exposure data. Hazard data used for this research are tephra and lahar, these two hazards of volcanoes consider as hazard that could damage the building. Probability of building damage is analyzed from building fragility curve due to tephra load. Exposure in this research use settlement building or house and population in disaster prone area. As the result, affected population need to be evacuated at Marapi prone area in 2020; 2025; and 2030 are 74.730; 78.360; and 81.283 with building damage are 17.125; 17.906; dan 18.790, and direct loss are Rp 1,07 Trilion; Rp1,15 Trilion; dan Rp1,23 Trilion. Affected population estimated at prone area of Guntur in 2020; 2025; and 2030 are 419.095; 442.599; dan 463.432 with building damage are 104.142; 109.484; and 114.912, and direct loss from the calculation are Rp9,9 Trilion; Rp10,7 Trilion; and Rp11,6 Trilion. Rinjani prone area have an estimation of affected people are 36.148; 37.676; and 39.253, building damage are 8.521 for 2020; and 9.353 for 2025 and 2030, and direct loss are Rp528 Billion; Rp593 Billion; and Rp615 Billion.